Inhibitory synapse dysfunction and epileptic susceptibility associated with KIF2A deletion in cortical interneurons - Ruiz-Reig, Nuria; García-Sánchez, Dario; Schakman, Olivier; Gailly, Philippe; Tissir, Fadel (Frontiers in Molecular Neuroscience, 2023)
Malformation of cortical development (MCD) is a family of neurodevelopmental disorders, which usually manifest with intellectual disability and early-life epileptic seizures. Mutations in genes encoding microtubules (MT) and MT-associated proteins are one of the most frequent causes of MCD in humans. KIF2A is an atypical kinesin that depolymerizes MT in ATP-dependent manner and regulates MT dynamics. In humans, single de novo mutations in KIF2A are associated with MCD with epileptic seizures, posterior pachygyria, microcephaly, and partial agenesis of corpus callosum. In this study, we conditionally ablated KIF2A in forebrain inhibitory neurons and assessed its role in development and function of inhibitory cortical circuits. We report that adult mice with specific deletion of KIF2A in GABAergic interneurons display abnormal behavior and increased susceptibility to epilepsy. KIF2A is essential for tangential migration of cortical interneurons, their positioning in the cerebral cortex, and for formation of inhibitory synapses in vivo. Our results shed light on how KIF2A deregulation triggers functional alterations in neuronal circuitries and contributes to epilepsy.